O właściwościach postępowania hybrydowego w regulacji ochrony konkurencji i konsumenta - Mrożek, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
This article describes the issue of replacing administrative regulations with civil law regulations. This is amulti-faceted problem, so the paper will focus on the example of the so-called hybrid proceedings, pending before the President of the Office of Competition and Consumer Protection. In the article, a brief comparison of the hybrid proceedings approach to classical administrative proceedings was initially conducted, pointing out that there was considerable uncertainty about compliance with the Constitutional division of power. The analysis of the proceedings before the President of the OCCP was presented, because of its links with the Constitution, indicating the disfunctionality of that authority at the time of the appeal. In the final section, research proposals and proposed changes were introduced, which consisted entirely of abandoning the hybrid model to the classic administrative model.
Keywords: President of the OCCP; administrative regulations; civil law regulation; division of power; hybrid proceedings